Consumer Behavior during the Pandemic in Malaysia: A Study of Grab Mart - Kee, Daisy Mui Hung; Eng, Wei Khee; Davis, Eleanor Hazel; Nurjannah, Farhatin; Athirah, Fatin; Nair, Devika; Nair, Rajesh Kumar (Journal of The Community Development in Asia, 2023)
During the pandemic COVID-19, delivery service is in high demand in Malaysia due to the government's implementation of several movement control orders to stop the spreading of the disease. Goods delivery service provides consumers with various types of products such as groceries, packaged food, and healthcare products. The research focuses on the Grab Mart goods delivery service. A total of 100 Grab Mart consumers are expected to participate in this survey. The findings show the consumers use Grab Mart goods delivery service more during pandemic COVID-19.